Formation of trans-1,3-Pentadiene in Off-Flavor Food - IMAI, Koichi; ISHII, Rie; TAKANO, Mariko; YONEDA, Aoi; OSAKA, Ikue (Food Hygiene and Safety Science (Shokuhin Eiseigaku Zasshi), 2014)
The purpose of the present study is to investigate the production of trans-1,3-pentadiene in a sorbic acid-containing food which was the subject of a complaint that it was off-flavor. Penicillium sp. was isolated from the off-flavor food. The isolated Penicillium sp. was identified as Penicillium chrysogenum by DNA sequencing of the internal transcribed spacer region and the D1/D2 region of the 28S subunit. When P. chrysogenum was cultured in the presence of potassium sorbate, trans-1,3-pentadiene was produced and detected by GC-MS after solid-phase micro extraction. The production of trans-1,3-pentadiene by P. chrysogenum in the culture solution was pH-dependent. These results suggest that the production of trans-1,3-pentadiene in the off-flavor food was mainly due to the decomposition of sorbic acid by P. chrysogenum.